TEACHING READING NARRATIVE READING BY USING LITERATURE CIRCLES STRATEGY TO THE TENTH GRADE STUDENTS OF SMAN 1 LEMPUING JAYA - nofitarina nofitarina (Edukasi, 2017)
The objective of this study are to find out whether or not there is significant difference and significant improvement on the tenth grade students’ narrative reading achievement between those who are taught by using Literature Circles Strategy and those who are not of SMA N 1 Lempuing Jaya. In this study, quasi experimental design was used. The sample of the study was taken by using purposive sampling technique and selected class X MIA 1 as the control group and X MIA 3 as an experimental group in academic year 2016/2017 that consisted of 71 students. This study was conducted for about a month and a half consist of fourteen meeting including pre-test and post-test. The instrument used in collecting the data was multiple choices test. The test was administrated twice, as the pre-test and post-test for both control and experimental group. The result of the test was analyzed by using independent sample t-test, pairead sample t-test and percentage analysis, it was found that there was significant different between students post-test experimental and control group, since p-output (0.002) was lower 0.05 and t-value (3.228) was higher than t-table (1.9949). Furthermore, there were significant improvement both of group, since p-output (0.000) was lower than 0.05 and t-value (16.785) in experimental group, and (7.628) in control group were higher than t-table (2.0301).